Molecular characterization of equine rotavirus group A detected in Argentinean foals during 2009–2014 - Miño, Samuel (2017)
Equine rotavirus group A (RVA) has been detected in several countries worldwide since its first detection in 1975. Currently, equine RVA is considered the major cause of dehydrating diarrhea in foals younger than 3 months, and the frequency of detection in clinical cases varies from 20% to 77%. The genotypes of epidemiologic relevance found in horses are G3P [12] and G14P[12]. In a survey conducted in Argentina from 1992 to 2008, equine RVA was detected in 21% and 39% of the fecal samples and outbreaks, respectively. Genotype distribution was 51% G3P[12] and 33% G14P[12]. In continuation with the surveillance, the aim of the present study was to characterize the equine RVA detected in Thoroughbred foals in Argentina from 2009 to 2014. A total of 436 stool samples (corresponding to 177 single diarrhea cases or outbreaks) were analyzed. Equine RVA was detected in 31% (135 of 436) of the samples, which corresponded to 42% (74 of 177) of outbreaks. From the positive cases, 42% (57 of 135) were genotyped. Of this, 63% were G3 (36 of 57) and 37% (21 of 57) were G14 genotype. Considering the whole data (1992–2014), equine RVA was detected in 25% (300 of 1,207) of the stool samples and 41% (119 of 293) of the diarrhea outbreaks. The results of this study also show a cyclic pattern of the G3 and G14 prevalence in the horse population with a change in G3:G14 frequencies from year to year. Furthermore, clustering in the phylogenetic tree suggests evolutionary and geographic relationships between the Argentinean strains compared with the strain circulating worldwide.